Effect of Knowledge Management Practices on the Performance of Nepalese Financial Institutions - Khanal, Lekhanath; Paudyal, Santosh Raj (Journal of Advanced Academic Research, 2018)
Knowledge Management (KM) is considered as a recent phenomenon prevailing in the management circle. Despite its growing concern, there are relatively few literatures showing clear linkage between knowledge management and organizational performance (OP) in financial sector. The main objective of this study is to measure the effect of knowledge management practices on the performance of financial institutions in Nepal. In this study, samples of 385 respondents were selected randomly from four different types of financial institutions of Kathmandu, Nepal. The statistical analysis was done to draw the conclusion. The results clearly showed that components of KM process (KM obtaining, KM organizing & KM applying) are positively correlated with the organizational performance measured in terms of Financial and Market Results, Organizational Effectiveness, Employee Satisfaction and Customer Satisfaction. Finally, this paper concludes that performance of any financial institution is significantly affected by various KM processes and practices adopted by these organizations.